Breast cancer awareness and breast self-examination practice among women in the rural field practice area of a medical college, Karnataka - Jaswanth, Swapna; A. C., Shyam; Manjunatha, Shashikala (International Journal Of Community Medicine And Public Health, 2022)
Background: Breast cancer is an important cause of morbidity and mortality among women in the developing world, which is also highly amenable for prevention and treatment, with regular screening methods. Methods: A cross sectional study was conducted among rural women. A total of 516 women above 18 years, from rural field practice area, participated in the study. A predesigned semi-structured study instrument was used to collect the data through interview method. Results: Among the 516 participants, 285 (55%) have never heard of breast cancer, media (56%) was the commonest source of information about breast cancer, 444 (86%) of them never knew what breast self examination, and only 43 (8.3%) were ever taught on how to do BSE and 37 (7%) practiced BSE. Conclusions: There was a low level of awareness on breast cancer and BSE as well as low practice of BSE among women in rural area of Karnataka, hence there is a need to increase the level of awareness on breast cancer and practice of BSE through health education programme by integrating with primary health care facilities for appropriate care, treatment and referral.